2018
DOI: 10.5539/ies.v11n10p16
|View full text |Cite
|
Sign up to set email alerts
|

Use of Slowmation in Biology Teaching

Abstract: The purpose of the study was to investigate the views of preservice teachers about use of slowmation in biology teaching. In the study, descriptive model was used. The participants were 12 third-grade preservice teachers in the department of Biology Education at Ziya Gökalp Education Faculty of Dicle University in the Spring Term of the academic year of 2016-2017. The research data were collected via observations and semi-structured interviews. In the research process slowmation activities were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Nordin and Osman (2018) found that student-generated SMA can be effective in fostering collaborative problem-solving skills in terms of establishing and maintaining shared understanding and group organization toward finding the appropriate action to solve a physics problem in secondary education. The results of some studies also revealed that the SMA task contributed to the development of twenty-first-century skills such as creativity, communication, and cooperation skills, information literacy, research skills, technology, and media literacy skills (Atalay and Belet Boyaci 2019;Karakoyun and Yapıcı 2018). Skills in using technology, such as taking photos with digital cameras, were also reported as an outcome of intentionally teaching using SMA in early childhood science classes (Fleer and Hoban 2012).…”
Section: Non-cognitive Learning Outcomesmentioning
confidence: 99%
“…Nordin and Osman (2018) found that student-generated SMA can be effective in fostering collaborative problem-solving skills in terms of establishing and maintaining shared understanding and group organization toward finding the appropriate action to solve a physics problem in secondary education. The results of some studies also revealed that the SMA task contributed to the development of twenty-first-century skills such as creativity, communication, and cooperation skills, information literacy, research skills, technology, and media literacy skills (Atalay and Belet Boyaci 2019;Karakoyun and Yapıcı 2018). Skills in using technology, such as taking photos with digital cameras, were also reported as an outcome of intentionally teaching using SMA in early childhood science classes (Fleer and Hoban 2012).…”
Section: Non-cognitive Learning Outcomesmentioning
confidence: 99%
“…In the dimension of learning and renewal, 21st century skills showed positive improvements in creativity and renewal, critical thinking and problem solving, communication and cooperation skills. The technique also contributes to the understanding of difficult and difficult subjects using simple materials, is effective in understanding abstract subjects, and, at the same time, students actively participate and contribute to their creativity (Atalay & Belet Boyacı, 2019;Chang et al, 2009;Ekici & Ekici, 2011;Fleer & Hoban, 2012;Hoban & Nielsen, 2010Karakoyun & Yapıcı, 2018;Uzun & Karaman, 2015). Further, studies have shown that slow-motion animation develops the mental models of students (Akaygun 2016; Church et al 2007;Mills et al 2018;Uzun, 2015).…”
Section: Slow-motion Animationmentioning
confidence: 99%
“…Furthermore, it is claimed that this approach stimulate skills prioritized in the , 21 st century, like communication, collaboration and creativity (e.g. Karakoyun & Yapici, 2018).…”
Section: Student-generated Stop-motion Animationsmentioning
confidence: 99%